Molecular mechanisms that restrict yeast centrosome duplication to one event per cell cycle - Elserafy, Menattallah; Neuner, Annett; Lin, Dennis Tien-chen; Zhang, Wanlu; Seybold, Christian; Schiebel, Elmar (Current biology, 2014)
Background - The spindle pole body (SPB) of budding yeast is the functional equivalent of the mammalian centrosome. Like the centrosome, the SPB duplicates once per cell cycle. The new SPB assembles adjacent to the mother SPB at a substructure called the bridge. The half-bridge, the bridge precursor, is a one-sided extension of the SPB central plaque layered on both sides of the nuclear envelope. Parallel Sfi1 molecules longitudinally span the half-bridge with their N termini embedded in the SPB central plaque, whereas their C termini mark the half-bridge distal end. In early G1, half-bridge elongation by antiparallel C-to-C dimerization of Sfi1 exposes free N-Sfi1 where the new SPB assembles. After SPB duplication, the dimerized Sfi1 is severed to allow spindle formation and SPB reduplication. - Results - We show that Sfi1 C-terminal domain harbors phosphorylation sites for Cdk1 and the polo-like kinase Cdc5. Cdk1 and, to a lesser extent, Cdc5 inhibit SPB duplication as phosphomimetic sfi1 mutations lead to metaphase cells with a single SPB. In contrast, phosphoinhibitory sfi1 mutations in Cdk1 sites are lethal because cells fail to sever the bridge after SPB duplication. Moreover, Cdc14 dephosphorylates C-Sfi1 to prepare it for a new round of duplication, and the kinase Mps1 promotes Sfi1 extension in G1. - Conclusions - Positive (Cdc14) and negative (Cdk1 and Cdc5) SPB duplication signals are integrated at the level of the half-bridge component Sfi1. In addition, Mps1 activates Sfi1 duplication. Fluctuating activities of these regulators ensure one SPB duplication event per cell cycle.